Normative dimensions' preferences towards intention to purchase green food product - Rahim, Hairazi; Shamsudin, Mad Nasir; Radam, Alias; Mohamed, Zainal Abidin (IDOSI Publications, 2011)
Normative dimensions constitute one of the important elements in the Theory of Reasoned Action (TORA) model. However, the changes of lifestyle over period and different societies have spurred the TORA model constitution and also to vary interpretation of the model itself towards intention to purchase the green food product. Therefore, this paper aims to explore the underlying dimensions of normative factor that may have the relationships with consumers’ intention behavior to purchase the green food product and determine the relationships among Malaysian consumers through the questions, both on salient referents, motivation to comply and intention subject to the green food product using six-point Likert scale (1 representing definitely disagree, unimportant and not purchase while 6 representing definitely agree, important and purchase). A total of 600 respondents were interviewed via structured questionnaire where they need to rank their agreement and importance level of statements given in the questionnaire to gather information of the normative dimensions that influence them to purchase the green food product. Based on the analyses of the study, the underlying dimensions from the factorization of norms have been found to be positively correlated to the Malaysian consumers’ intention to purchase the green food products among the Malaysian consumers.